VARIETAL DIVERSITY IN THE FRAGARIA ANANASSA DUCH CROP. - Rozhko І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The global demand for pineapple strawberries continues to grow, especially in Asia, North and Central America, and North Africa. Cultivar selection is a key factor in establishing productive and high-quality commercial plantations of F. ananassa Duch. Cultivar diversity in the crop allows growers to adapt to the needs of today's demanding climate-oriented market by offering different types of products: fresh fruit, processed products, organic fruit, etc. According to statistics from the FAO's annual report, presented by the World Population Review, global demand for pineapple strawberries continues to grow, with China, the United States, and Egypt leading the world's production. In 2023, global production amounted to more than 8.8 million tons, with the lion's share produced by China (3 336 690 tons), the USA (1 055 963 tons), and Egypt (597 029 tons). Asia is the largest continental producer (4.53 million tons), followed by America, Europe, Africa, and Oceania. Geographical differences in the countries that commercially grow F. ananassa Duch. (76 of them are on the official list) affect the choice of cultivated varieties, which have different requirements for environmental conditions, ripening, and harvesting seasons. In moderate regions, strawberries are harvested in early summer, while in equatorial regions, they can be grown throughout the year. Cultivation technologies also vary. The stable success of global production of F. ananassa Duch. is explained by an integrated approach that includes a breeding component (development and introduction of varieties with prioritized traits such as cold resistance, drought resistance, pest resistance, and suitability for specific production and processing technologies, taking into account consumer preferences) and optimized production systems that consider climatic fluctuations in yields. According to the World Population Review, the most popular commercial varieties of pineapple strawberries grown in the main producing countries are: “Sweet Charlie”, “Festival”, “Camarosa”, “Albion”, “San Andreas”, “Clery”, “Marmolada”, and “Sonata”. In Ukraine, the most popular varieties of national selection are those that provide maximum profit due to early or late ripening or have the appropriate parameters for technological processing (e.g., freezing). These include early and medium-early varieties such as “Rosana Kyivska”, “Olvia”, and “Veselka”; medium-ripening varieties such as “Herkules”, “Prysviata”, and “Perlyna”; medium-late varieties such as “Prezent”; and late varieties such as “Atlantyda”. Among the short-day varieties of foreign selection are early and medium-early varieties such as “Honey” and “Elsanta”; mid-season varieties such as “Elegance” and “Sonata”; and late varieties such as “Polka” and “Galia CIV”. Among the “neutral day” varieties are “Albion”, “Aromas”, and “Portola”.